Osseous plate alkaline phosphatase is anchored by GPI. - Pizauro, J. M. [UNESP]; Ciancaglini, P. [UNESP]; Leone, F. A. [UNESP] (My University, 1994)
Alkaline phosphatase activity was released up to 100% from the membrane by using 0.1 U of phosphatidylinositol-specific phospholipase C from B. thuringiensis. The M(r) of solubilized enzyme was 145,000 by Sephacryl S-300 gel filtration and 66,000 by SDS-PAGE, suggesting a dimeric structure. Solubilization of the membrane-bound enzyme with phospholipase C did not destroy its ability to hydrolyze p-nitrophenyl phosphate (PNPP) (264.3 mumol min-1 mg-1),ATP (42.0 mumol min-1 mg-1) and pyrophosphate (28.4 mumol min-1 mg-1). The hydrolysis of ATP and PNPP by solubilized enzyme exhibited Michaelian kinetics with K0.5 = 70 and 979 microM, respectively. For pyrophosphate, K0.5 was 128 microM and site-site interactions were observed (n = 1.4). Magnesium ions were stimulatory (Kd = 1.5 mM) but zinc ions were powerful non-competitive inhibitors (Kd = 6.2 microM) of solubilized enzyme. Treatment of solubilized alkaline phosphatase with Chellex 100 reduced the original PNPPase activity to 5%. Cobalt (K0.5 = 10.1 microM), magnesium (K0.5 = 29.5 microM) and manganese ions (K0.5 = 5 microM) restored the activity of the apoenzyme with positive cooperativity, suggesting that phosphatidylinositol-specific phospholipase C-solubilized alkaline phosphatase is a metalloenzyme. The stimulation of the apoenzyme by calcium ions (K0.5 = 653 microM) was lower than that observed for the other ions (26%) and exhibited site-site interactions (n = 0.7). Zinc ions had no effect on the apoenzyme of the solubilized enzyme.